Invalidity of SUV Measurements of Lesions in Close Proximity to Hot Sources due to “Shine-Through” Effect on FDG PET-CT Interpretation - Yiyan Liu (Radiology Research and Practice)
It is well known that many technical and physiologic factors can affect the reliability of the standardized uptake value (SUV) on FDG PET-CT. Another potential problem of which we may be aware but has not been previously discussed is significant SUV overestimation of lesions in the direct neighborhood of large hot sources, namely, areas with high FDG uptake or activity such as a tumor, myocardium, urinary bladder, kidney, or gastrointestinal tract. The magnitude of SUV overestimation of the lesions directly neighboring the large hot sources is varied among the different cases, and it is possibly secondary to “shine-through” effect of the hot sources, which would warrant further systematic investigation such as phantom simulation experiment. If the lesion is in the close territory of the hot source, measured SUV is often overestimated and invalid. Visual interpretation should be used for evaluation of FDG avidity of the lesion.